2022
DOI: 10.1186/s12884-022-04510-8
|View full text |Cite
|
Sign up to set email alerts
|

Planned vaginal and planned cesarean delivery outcomes in pregnancies complicated with pregestational type 1 diabetes – A three-year academic tertiary hospital cohort study

Abstract: Background Finland has the world’s highest incidence of 62.5/100000 of diabetes mellitus type 1 (DM1) with approximately 400 (1%) DM1 pregnancies annually. Pregnancies complicated by DM1 are accompanied with increased risk for perinatal morbidity and mortality. Timing and mode of delivery are based on the risk of complications, yet the data on labor induction is limited. The aim of this study was to compare delivery outcomes in planned vaginal (VD) and planned cesarean deliveries (CD) in late p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
4
2
Order By: Relevance
“…In GDM, unexpected and different outcomes between this research and previous studies described that almost half of the patients delivered by CS and the other half delivered vaginally, but this differs from a study done in Saudi Arabia (SA) in which vaginal delivery was more common than CS [8,[17][18][19]. In pre-GDM, unexpected and different outcomes between this study and previous studies described vaginal delivery as more common than CS [8,20]. It was also noted that that not all patients who undergo CS should be viewed as having unfavorable pregnancy outcomes; instead, CS is frequently suggested as a preventive measure used by healthcare professionals to reduce the risk of perinatal problems brought on by maternal diabetes [21].…”
Section: Discussioncontrasting
confidence: 84%
“…In GDM, unexpected and different outcomes between this research and previous studies described that almost half of the patients delivered by CS and the other half delivered vaginally, but this differs from a study done in Saudi Arabia (SA) in which vaginal delivery was more common than CS [8,[17][18][19]. In pre-GDM, unexpected and different outcomes between this study and previous studies described vaginal delivery as more common than CS [8,20]. It was also noted that that not all patients who undergo CS should be viewed as having unfavorable pregnancy outcomes; instead, CS is frequently suggested as a preventive measure used by healthcare professionals to reduce the risk of perinatal problems brought on by maternal diabetes [21].…”
Section: Discussioncontrasting
confidence: 84%
“…Several studies have shown that the rate of cesarean section and postpartum hemorrhage in patients with GDM is significantly higher than that in women without GDM (3)(4)(5)(6), and more than 30% of cesarean sections in patients with GDM are due to failed vaginal birth (7). Failed vaginal delivery trial and postpartum hemorrhage are associated with uterine atony (8,9), suggesting that GDM affects uterine contractility. An in vitro trial of isolated uteri in patients with diabetes confirmed that high glucose levels caused poor uterine contractility (10).…”
Section: Introductionmentioning
confidence: 99%
“…[17] Found a positive relationship between the growth of the mean glucose value and the value of Large for Gestational Age-LGA and neonatal composite outcome-NCO. [18] consider the difference between Vaginal Delivery-VD and Caesarean Delivery-CD in a sample of Finnish women in childbirth characterized by gestational diabetes mellitus. The authors verify that the adverse consequences of childbirth tend to be greater in the case of using Caesarean Delivery-CD than with Vaginal Delivery-VD.…”
Section: Literature Reviewmentioning
confidence: 99%